The complete mitochondrial genome sequence of Crenidorsum turpiniae (Hemiptera: Aleyrodidae) - Shuai Li; Wei-Rui Wang; Yu-Feng Zhou; Li-Kun Zhong; Yan Jiang; Ze-Hong Meng (Mitochondrial DNA. Part B. Resources, 2020)
We determined the complete mitochondrial genomes of Crenidorsum turpiniae, a new record whitefly pest on tea-tree. The mitogenome of C. turpiniae is 15,427 bp long and consists of 13 protein-coding genes, 22 tRNA genes, two rRNA genes and a putative control region (GenBank: MN934936). The whole base composition of the heavy strand for A, C, G and T is 30%, 12.24%, 15.82% and 41.87%, respectively, with an AT bias (-16%). All PCGs use ATN as start codon (N, any nucleotide), except for NAD6 uses TTG. Most of the PCGs use TAA as a stop codon. The length of 16SrRNA and 12SrRNA gene are 1277 bp and 768 bp, respectively. Phylogenetic analysis indicated that C. turpiniae and Tetraleurodes acaciae had a closer genetic relationship.